The viability of cooperative societies from the anarchist- cybernetics perspective: a systematic review of the field and research opportunities - Osejo Bucheli, Camilo (Ingeniería Solidaria, 2023)
Introduction: This article is part of an ongoing research project that started in 2022 and investigates the viability of cooperative associations from an anarchist-cybernetics perspective at the Universidad del Valle, Department of Administrative Sciences.Problem: Management Cybernetics and anarchism are fields with significant coincidences regarding organisational theory. From the point of view of anarchism, voluntary organisation is a form of exercising individual freedom, while in cybernetics, autonomy is the desirable state of organisation.Objective: The article aims to identify the current state of academic development in the field of anarchist-cybernetics, specifically around the concepts of “autogestión”, “self-management” and “self-control”.Methodology: The article proposes a systematic literature review of the last 10 years in nine academic databases.Results: The field presents research on radical political groups but lacks research on voluntary organisations such as cooperatives. The predominant research methods used are qualitative for empirical research, and non-empirical research is relevant in this field. Latin America and the developing economies are interesting fields for future development. Case studies and the historical method are relevant for the study of anarchy, and Beer´s VSM is the most used tool for cybernetics in this field.Conclusion: The field appears to be of great interest for various multi-decade old journals.Originality: This is one of the few research projects to link the organisational side of anarchism and management cybernetics. Anarchist-cybernetics is a novel subject after almost 60 years of not having any academic publications.Limitations: As a novel subject, not many publications fit the requirements for the review.
Keywords: autogestión; self-management; self-control; anarchism; cybernetics